Remaking Muslim politics : pluralism, contestation, democratization - Hefner, Robert W., 1952- (Princeton studies in Muslim politics., 2005)
There is a struggle for the hearts and minds of Muslims unfolding across the Islamic world. The conflict pits Muslims who support pluralism and democracy against others who insist such institutions are antithetical to Islam. With some 1.3 billion people worldwide professing Islam, the outcome of this contest is sure to be one of the defining political events of the twenty-first century. Bringing together twelve engaging essays by leading specialists focusing on individual countries, this pioneering book examines the social origins of civil-democratic Islam, its long-term prospects, its implicat.